High time to enhance dancer welfare: a call to action to improve safeguarding and abuse prevention in dance - Cumming, Jennifer; Nordin-Bates, Sanna M.; Johnson, Carrie; Sanchez, Erin N.; Karageanes, Steven J. (BMJ Open Sport & Exercise Medicine, 2024)
While there is a lack of research into abuse in elite dance, numerous allegations of emotional, sexual and physical abuse of dancers can be found anecdotally in the media, legal convictions and personal accounts. As more dancers speak out, the scale of the problem within preprofessional schools and professional companies is becoming apparent. Accordingly, effective safeguarding mechanisms for preventing, identifying and reporting abuse are urgently needed. This viewpoint is intended to raise health professionals’ awareness of factors contributing to abusive practices found in dance environments and the potential clinical implications of abuse to dancers’ health and well-being. We also call for research and policy engagement on safeguarding and abuse prevention designed and implemented in partnership with stakeholders, aiming to promote safe and positive dance environments for all.
Publisher: BMJ Specialist Journals Section: Viewpoint

Rethinking sexual violence labels: exploring the impact of ‘victim’ and ‘survivor’ discourse - O’Shea, Brittany; Feicht, Rebecca; Brown, Marion; Numer, Matthew (European Journal of Psychotraumatology, 2024)
Background: Universities’ responses to sexual violence have faced scrutiny for their lack of proactiveness and their failure to address campus socio-cultural norms that contribute to rape myth acceptance. The labels victim and survivor play a crucial role in shaping attitudes toward sexual violence, but there is limited research on how university students perceive these labels. Objective: This paper explores sexual violence labels and their role in perpetuating rape culture. Undergraduate university students’ beliefs on using the label survivor instead of victim to describe someone who has experienced sexual violence were examined to consider how these labels create societal discourse on sexual violence. Method: The study draws on qualitative data collected from undergraduate students in Canada and the United States through open-response questions in an interactive textbook. Data were analysed and interpreted using a multi-method approach that combined principles of Critical Discourse Analysis and Feminist Poststructuralism. Direct quotes and word clouds from participants’ responses are used as evidence and to visually display discourse. Results: Findings revealed that participants recognised the negative societal discourses associated with the label victim and supported using survivor to challenge perceptions of sexual violence. Despite this, participants expressed hesitancy to adopt the label survivor because of the potential negative implications, such as the label promoting the allocation of individual blame, increasing barriers to justice, and reducing the perceived severity of sexual violence. Conclusions: This study underscores the complexities of sexual violence labels, the influence of language in shaping societal perceptions, and the need for a more comprehensive and equitable approach to responding to sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence.Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence.Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence. Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence. Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20008066.2023.2296329
Keywords: Bibliographie; Nettoyer

Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Publisher: SAGE Publications
Keywords: Bibliographie

Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2022.2149599
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

The art of Jane Orleman: childhood trauma and the discourse of sexual violence - Kwon, Hyunji (Journal of Gender Studies, 2023)
Jane Orleman (American, born 1942) is an artist and a survivor of child sexual abuse. Through paintings she created during therapy, Orleman rejects the gendered and patriarchal binaries between therapeutic art and professional art, which pit the private, feminine, and intuitive against the public, masculine, and intellectual. By analysing selected artworks from Orleman that embody her child self, young woman self, and alternative self, I propose that Orleman reflects on and challenges the pathology of sexual trauma along with the discourse of sexual violence as a political statement. Therefore, I argue that her art deserves to be part of a larger, counternarrative, anti-rape and anti-incest cycle in contemporary American art.
Publisher: Routledge _eprint: https://doi.org/10.1080/09589236.2022.2064838
Keywords: Sexual violence; art; survivor; therapy; trauma

The sound of misogyny: sexual harassment and sexual violence in the music industry - McCarry, Melanie; Käkelä, Emmaleena; Jones, Cassandra; Manoussaki, Kallia (Journal of Gender-Based Violence, 2023)
The cultural and creative industries are the fastest growing industries in the UK (). Stakeholder engagement, media reporting, anecdotal evidence and emerging research suggests that there are endemic levels of sexual harassment and sexualised violence within the music industry that can be described as widespread, systemic and normalised. This article reviews the literature on sexual harassment and sexualised violence in the music industry, examining gender stratifications and inequalities within the music industry with a focus on UK, Australian and US studies. The music industry is not a singular entity but instead, is an agglomeration of many different sub-sectors predominantly consisting of three interconnected spheres of music recording and distribution, music publishing and licensing, and live performance. This paper references Kelly’s (; ; ) theorisations on conducive contexts and the continuum of violence to argue that historical and entrenched misogyny and sexism along with the lack of regulation, process and governing frameworks create conditions for both the maintenance of gender inequality and the perpetuation of sexual harassment and sexualised violence within the music industry. Consequently, both the cultural context and the practice of misogyny (in this case sexual harassment and sexualised violence) within the music industry are mutually supporting and reinforcing.
Publisher: Policy Press Section: Journal of Gender-Based Violence
Keywords: Misogyny; Music; Myriam

Au-delà des « vagues » #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017–2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections, 2023)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant d’abord dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes et ce, au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années (2017–2022). Dans la seconde partie, les autrices détaillent les travaux du réseau D!G , lancé en avril 2021 par Vanessa Blais-Tremblay, et présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ». , This article profiles five organizations that have been advocating for equity in Quebec music since 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL and D!G Différences et inégalités de genre dans la musique au Québec. In line with a long tradition of critical work in feminist historiography, the authors first account for the diversity of feminist mobilizations in Quebec music beyond the #metoo “waves” which have received significant media attention over the past five years (2017–2022). In the second part, the authors detail the development of the D!G network, a feminist collaborative research partnership launched in April 2021 by Vanessa Blais-Tremblay, and its contributions to both Quebec’s music industry and to feminist partnership research epistemologies and methodologies.
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12906
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

Que reste-t-il de nos humours ?À la recherche d’un rire de gauche - Quemener, Nelly (Revue du Crieur, 2023)
Les enjeux liés aux luttes menées par les personnes trans’ sont une parfaite illustration du fait que la visibilité ne suffit pas et qu’elle peut même parfois se révéler préjudiciable. En effet, depuis quelques mois, la presse, la télévision, la radio s’agitent dès qu’une actualité touche de près ou de loin à la transidentité. Actuellement, les voix des trans’ sont encore trop souvent couvertes par les discours cis’, lesquels tendent également à délégitimer les savoirs produits par et pour des trans’. Il est grand temps de retourner la lunette : au lieu de scruter les personnes trans’ – leur transition –, il est urgent de les lire et de les écouter. Ces expériences-là ont certes des choses à apprendre aux personnes cis’ : bien sûr que l’on comprend mieux ce qu’est le genre face à des personnes qui ont fait l’expérience de quitter celui qui leur a été assigné à la naissance, bien sûr que cela rend plus insupportable encore la rigidité des normes de genre, binaires et arbitraires jusqu’à l’absurde. Mais au-delà de ce que les cis’ peuvent apprendre des trans’ pour mieux se comprendre elles-mêmes et eux-mêmes, au-delà de cette lecture instrumentale, il s’agit désormais de laisser les marges parler. Il s’agit de se concentrer sur les luttes sociales, les revendications portées par les personnes trans’ et les associations, de défendre les conditions matérielles d’existence des trans’, de lutter contre les nombreuses discriminations qui pèsent encore sur elles et eux, y compris contre celles qui limitent drastiquement leur accès aux positions permettant de produire légitimement du savoir, il s’agit de les laisser libres de définir leurs cadres de pensée et la manière dont ils, elles, iels souhaitent parler ou pas de leurs parcours. De les laisser, enfin, écrire leur histoire.
Place: Paris Publisher: La Découverte

Comedy’s double killjoy: workers’ DIY strategies to address harassment and precarity in the comedy industry - Trusolino, Madison; Ships, Diandra (Feminist Media Studies, 2023)
Since 2017, the #MeToo movement has highlighted gender-based violence and harassment in the comedy industry, where those comedians affected have little to no workplace infrastructure to lean on. Because comedy clubs are described as venues rather than sites of work, comedy workers are not technically employees and are not protected by workplace safety laws nor supported by professional organizations or unions. We argue that the lack of a formal workplace and its related precarity exacerbates violence against women, queer, transgender, disabled, and/or workers in the Canadian and American comedy industries, pushing comedy workers to enact do-it-yourself workplace safety strategies to protect themselves and one another. We describe these protective, caring activities as akin to Brenda Parker’s “double killjoy,” and push our understanding of creative work into places of public resistance and life-making.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2023.2229055
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

La Circassienne: A Study of the Female Circus Artist in French Literature - Menninga, Crystal (Masters Theses, 2022)

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1886141
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Que fait #MeToo à la littérature ? - Zenetti, Marie-Jeanne (Revue critique de fixxion française contemporaine, 2022)
Que fait #MeToo fait à la lecture, à la critique et à l’enseignement des textes littéraires ? Le mouvement #MeToo a contribué à une large prise de conscience quant aux enjeux linguistiques liés aux violences sexuelles et sexistes : lutter contre de ces violences suppose d’abord de nommer un viol un viol. Mais une telle exigence de désambiguïsation peut entrer en contradiction avec la complexité interprétative valorisée dans le cadre de la lecture littéraire. Elle présenterait par ailleurs le risque d'inviter à lire des textes éloignés de nous dans le temps et l’espace en les évaluant à l’aune de notions et d’une morale contemporaines jugées anachroniques. Prolongeant les réflexions récentes de Gisèle Sapiro (Peut-on dissocier l’œuvre de l’auteur ?) et d’Hélène Merlin-Kajman (La littérature à l’ère de MeToo), cet article étudie la réception du récit de Vanessa Springora, Le consentement (2020). En interrogeant la polarisation des discours critiques et théoriques entre une lecture “féministe” et une lecture “littéraire” parfois présentées comme incompatibles, il pose la question du lien possible entre violences sexuelles et pratiques interprétatives. Il théorise une pratique de lecture soucieuse de contextualiser l’usage des modèles interprétatifs mobilisés dans l’analyse littéraire et de les critiquer en interrogeant les rapports de pouvoir qu’ils dissimulent. Il défend ainsi l’hypothèse que le mouvement #MeToo invite les littéraires à réévaluer leurs pratiques et leurs paradigmes de lecture en fonction de ce qu’ils rendent possible.
Number: 24 Publisher: Ghent University
Keywords: #metoo; Irina; consentement; lecture féministe; lecture littéraire; violences sexuelles

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Publisher: SAGE Publications Ltd
Keywords: Myriam; TV; TV production; Television

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2020.1759114
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Number: 2
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

“#UsToo”: Empowerment and Protectionism in Responses to Sexual Abuse of Women with Intellectual Disabilities - Boux, Holly Jeanine (Berkeley Journal of Gender, Law & Justice, 2022)
Publisher: Berkeley Journal of Gender, Law & Justice
Keywords: Bibliographie; Nettoyer

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

“My work opportunities depend on how much I can take” : inappropriate behaviour and harassment in the cultural domain in Finland - Jaakola, Meri (2022)
Phenomena of inappropriate behaviour and harassment are neither new nor unique to the cultural domain. However, these phenomena have not been largely publicly discussed before the 2017 me too movement, presumably due to the culture of silence prominent within the cultural domain. After the movement that started from the film industry and quickly spread around the world, discussion on ethical working conditions has arisen within all the cultural domain as well. This qualitative driven mixed methods research reviews the current situation of inappropriate behaviour and harassment in Finland and seeks to understand the magnitude and forms of the phenomena. The research questions are: 1) What special characteristics or structures in the arts and culture field enable inappropriate behaviour and harassment or the possibility of them? And 2) What can be done to eliminate inappropriate behaviour and harassment from arts and culture workplaces? The research questions are answered analyzing research data collected using a survey and six themed interviews. Research data was collected in the spring of 2021. Topics that surfaced from the survey were used as a basis for the interview questions. Findings from the survey and the interviews act as the thematical scope of this master’s thesis, as they are the most important themes to come out of this research. The main findings of the thesis are that there are four elements that enable and maintain the improper working culture within the cultural domain. The elements are insufficient funding, poor management, artist myth, and limitlessness of the work. These themes are examined in discussion with literature. The four steps this thesis suggests helping uproot the improper behaviour in the cultural domain according to the research data and literature are 1) Pushing for the cultural domain’s ethical board to be established, 2) Composing ethical guidelines for all the cultural domain, 3) Basing funding on following the said guidelines, and 4. Talking about improper behaviour publicly and bringing cases of misconduct forward.
Accepted: 2022-03-30T06:27:19Z Publisher: Taideyliopiston Sibelius-Akatemia

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

Briser le rideau de verre en humour - Morency, Sophie-Anne; Cézard, Zed; Carbonneau, Karine (2022)
Keywords: Sophie-Anne

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

Narrating women workers’ perceptions of sexism and change in the Australian screen postproduction sector before and after #MeToo - Dooley, Kath; Erhart, Julia (Feminist Media Studies, 2021)
This article interrogates the localized experiences of present-day workers who identify as women in Australian postproduction sectors, including editing, visual effects (VFX), and animation, exploring sex ism and perceptions of change in the age of #MeToo. Considering the significant numbers of women working in these sectors, and the scant research into their experiences undertaken in an Australian context, the authors conducted semi-structured interviews with ten women in various roles and in various geographical locations in Australia. This qualitative approach to data collection aims to explore inequalities that may not be captured in industry surveys, providing fine-grain details of the ways that individuals in postproduction experience sexism. The resulting data suggests that while there is continuity between the gendered experiences of these workers and that of women in industry sectors that have already been documen ted, there are, however, new observations about changes in work place behavior in the sector, brought about by growing public awareness of industry discrimination and harassment and of shifts in Australian industry policy. The authors isolated recurring themes within women’s gendered experiences in relation to how they per ceived the impact of the gender-equity initiatives on the attitudes of their co-workers, their workplace opportunities, and their experi ences as workers.
Keywords: Irina

Indian Women in Comedy: : An Inquiry into the Perpetuation of Rape Culture on Social Media - Sharma, Mridula (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
‘Postfeminist’ society has created the impression that contemporary discourses on gender representation, particularly in digital media platforms, are pointless. This misconception is coupled with online aggression by men’s rights activists who position feminist debates as sources of male oppression. However, media practices and consumption processes continue to maintain the supremacy of the male gender identity, which strengthens the process of transforming social media into a component of the “manosphere.” The failure of the fourth wave of feminism in utilising the Internet for mobilising activism for the ontological equality of all genders has succeeded by increasing gender-based violence against women. Indian women in comedy negotiate with these systemic inequalities while navigating male dominance in the comedy industry. The paper is an attempt to examine the structures of gender inequality and bias that affect the participation and advancement of women in the comedy circuit. Its focus remains on the formulation of a rape culture on social media and its subsequent consequences in the larger social context of the development of a patriarchal culture.
Number: 2
Keywords: Digital Abuse; Sophie-Anne

“The balance of power is me: 0, Harvey Weinstein: 10”: A Critical Discourse Analysis of the press representation of Hollywood’s biggest sexual harassment scandal - Nikolova, Evelin (Women's Studies International Forum, 2021)
On 5 October 2017, The New York Times published an article in which Harvey Weinstein was accused of sexual harassment by five women. The scandal grew to enormous proportions as more allegations against him followed. This led to the #MeToo and TIME'S UP movements, initiatives to fight sexual harassment in the workplace. Given that media discourse can have an impact on the knowledge, beliefs, attitudes, and behaviours of the public regarding these phenomena (van Dijk 1989), this study adopts a Critical Discourse Studies (CDS) perspective and explores how power and gender inequality are sustained, (re)shaped and/or challenged by focusing on the reporting of the Harvey Weinstein case which - to the author's best knowledge - has not been analysed before in the field of linguistics. It draws from the systemic functional linguistics and the discourse-historical approach and it examines the way the perpetrator, the accusers and the phenomenon of sexual harassment were discursively constructed in five key articles published in the New York Times. The findings differ in a major way from existing research on sexual violence against women in that 1) the perpetrator, Weinstein, was depicted with clear ascription of agency, 2) women victims' voices and feelings were foregrounded, 3) the link between sexual harassment and the social context in which it occurs was discussed.
Keywords: Critical discourse studies; Discourse-Historical Approach; Discursive strategies; Media representation; Myriam; Sexual harassment; Transitivity analysis; Weinstein

“Just a Junior Journalist”: Field Theory and Editorial Photographers’ Gendered Experiences - Somerstein, Rachel (Journalism Practice, 2021)
Women outnumber men in graduate and undergraduate programs in photojournalism and work as photo editors at a number of high-profile publications. But in the field of professional editorial photography, they lag men in pay, legitimacy, and status. Using Bourdieu’s field theory, this paper explores how gender shapes the way women experience, compete in, and negotiate the field, specifically regarding assignments, salary, sexual harassment, and tactics for achieving access to stories. Findings suggest that women use their gender as a competitive advantage however they can, but that negative capital attached to femaleness and femininity persists. The findings are based on semi-structured interviews conducted between 2017 and 2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats.
Publisher: Routledge _eprint: https://doi.org/10.1080/17512786.2020.1755345
Keywords: Field theory; Myriam; gender; journalism; photojournalism; women and photography

Normalising sexualised violence in popular culture: eroding, erasing and controlling women in rock music - Hill, Rosemary Lucy; Richards, Daisy; Savigny, Heather (Feminist Media Studies, 2021)
How does music play a role in normalising men’s sexual violence towards women? Using mainstream rock and metal music as an illustrative case study, we offer a nuanced account of the ways in which men’s sexual violence is normalised. Using a definition of sexual violence drawn from Liz Kelly’s notion of a continuum, which reframes sexual violence as the loss of women’s ability to control sexual experiences, we explore the ways in which sexual violence is a prevalent lyrical and audio-visual component of rock and metal songs. We show that a pernicious theme of rock and metal over the last 25 years is the erosion of women’s ability to refuse sexual activity and to have voice and be heard. We argue that this erosion of women’s consent takes place through the representational use of emotional abuse, controlling/coercive behaviour, and through the objectification of women. The erasure of consent presented through these methods becomes a key means of establishing sexual control. Through manipulation, the confusion of what counts as sexual violence and how it is defined, men’s sexual violence against women is normalised.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1902368
Keywords: Feminism; music video; rock lyrics; rock music; sexual violence

Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer

A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari; Jordan, Ana; Jameson, Jill; Davy, Zowie (Violence Against Women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.
Keywords: Camille

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Keywords: Bibliographie; Nettoyer

L’opéra, un monde professionnel hanté par les violences de genre - Buscatto, Marie; Helbert, Soline; Roharik, Ionela (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Le 19 août 2020, la soprano Chloé Briot dénonce dans La Lettre du Musicien des agressions sexuelles répétées portées par un collègue chanteur lors de la production de l’opéra L’inondation. Faute d’avoir été entendue et défendue par sa direction, elle annonce encore avoir porté plainte devant la justice française dès le mois de mars de la même année et vouloir ainsi « en finir avec la loi du silence ». Pourquoi l’artiste lyrique n’a-t-elle pas été entendue à plusieurs reprises malgré ses plaintes auprès de ses collègues et de la production ? Dans quelle mesure cette agression sexuelle est-elle symptomatique d’un mode de fonctionnement sexiste plus large du monde de l’opéra français ? Peut-on parler effectivement d’une « loi du silence » dénoncée par la chanteuse ? Si oui, que risquent ceux et celles qui dénonceraient des faits sexistes et des violences sexuelles ?
Publisher: Société québécoise de recherche en musique
Keywords: Bibliographie; Nettoyer

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

Why We Should Avoid Artists Who Cause Harm: Support as Enabling Harm - Elicker, Bradley (Journal of Applied Philosophy, 2021)
This article examines our ethical responsibility toward artists engaged in harmful behaviors. Specifically, I demonstrate when and why we are morally obligated to withdraw our public and financial support from Artists Who Cause Harm such as Louis C.K., Terry Richardson, and Ryan Adams. Using a moral distinction presented by Philippa Foot and others, I identify this support as enabling harm when the wealth and influence that we support removes typical barriers that protect victims from harm and interposes barriers that prevent victims from avoiding harm. I proceed to demonstrate that our personal support is morally significant, and we have a moral responsibility to make contributions to collective action when the cost is low or the degree of belief that others will contribute is high. Here we have both a strong belief that others will withdraw support and a relatively low cost to ourselves to do so. I acknowledge that enabling current harms is only a sufficient condition to withdrawing support from an artist and should not minimize other reasons for avoiding certain artists and their works. However, when we do believe that our support enables an artist engaged in harmful behaviors, we have an obligation to withdraw that support.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/japp.12467
Keywords: Bibliographie

#MeToo In Polish Theatre Education - Kwaśniewska-Mikuła, Monika (Philosophy, Sociology, Psychology and History, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Krytyczki as Activists: On Theatre Criticism, Affect, Objectivism and #MeToo in Polish Drama Schools: Interview with Monika Kwaśniewska - Lech, Kasia (Critical Stages/Scènes critiques, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

An Examination on Sexual Harassment Activities in the South African Professional Performing Arts Industry - Yende, Sakhiseni Joseph (Journal of African Films & Diaspora Studies, 2021)
Keywords: Bibliographie; Nettoyer; Patriarchal power; Performing arts industry; Professional theatres; Raphaël; Sexual harassment; Women in theatre

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

#MeToo in Sweden: Museum Collections, Digital Archiving and Hashtag Visuality - Uimonen, Paula (Ethnos, 2020)
In October 2017, the Nordic Museum in Stockholm launched its #metoo collection. The aim was to capture the viral #MeToo campaign that in Sweden has been likened to a (feminist) revolution. Based on archival research, interviews and media analysis, this article explores public submissions to the #metoo collection and analyses the museum’s rationale for collecting what is considered to be difficult cultural heritage. Noting the absence of images in the collection, the article argues that the iconic hashtag #MeToo constitutes an alternative form of digital visuality, here termed hashtag visuality. Hashtag visuality, the article suggests, is an emerging form of visual representation that captures the multimodal logic of social media, blurring distinctions between texts and images. In Sweden, #MeToo hashtag visuality reveals the contradictory prevalence of structural sexism and sexual violence in a country with a national self-image of gender equality and a self-proclaimed feminist government, while affirming feminist agency.
Publisher: Routledge _eprint: https://doi.org/10.1080/00141844.2019.1640264
Keywords: Digital cultural heritage; Myriam; feminist agency; online testimonies; sexual violence; viral campaign

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Publisher: Routledge _eprint: https://doi.org/10.1080/09589236.2020.1821178
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Me Too: The Effects of Sexual Harassment and Assault in the Entertainment Industry - Gaal, Cassandra (Backstage Pass, 2020)
Keywords: Entertainment Industry; Myriam

‘To draw light, you need shadow’: Using graphic art to counter gender based violence in Drawing the Line - Zare, Bonnie (South Asian Popular Culture, 2020)
Women in India cope with an ongoing sense of precarity owing to the frequency of street harassment and sexual violence; this impacts their freedom to travel and sense of autonomous agency. The December 2012 Nirbhaya case, the rape and fatal injury of a Delhi medical student, returned the subject of rape to public discourse leading to mass protests and, eventually, some stronger anti-rape laws; however, #metoo allegations surface weekly, and artists and activists are demanding that the trivialization of rape and verbal abuse stop and active steps be taken to dismantle the cultural scaffolding undergirding twomen's violation. In 2014 a collaboration by Zubaan Press (New Delhi) and the Goethe Institute (Germany) brought a group of Indian graphic artists together to create stories about women’s ground realities and the microaggressions they experience. The resulting publication, Drawing the Line: Indian Women Fight Back, contains fourteen vignettes which reveal the constraints women experience and also illuminate women’s capacity for resilience and boldness. This essay analyzes the forms of resistance imagined in these narratives, how particular stories illuminate slow violence, and what may be lost if we know little about the perpetrators who commit these acts against women.
Publisher: Routledge _eprint: https://doi.org/10.1080/14746689.2020.1775342
Keywords: Essay; India; Indian women; Myriam; Sexual harassment; Gender; graphic novel; sexuality; violence

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Publisher: Edinburgh University Press
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

Mobilisations féministes sur Facebook et Twitter: Le cas du mouvement #StopCultureDuViol au Québec - Hübner, Lena A.; Pilote, Anne-Marie (Terminal, 2020)

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

Non-Consensual Sexual Contact at Electronic Dance Music Parties - Palamar, Joseph J.; Griffin, Marybec (Archives of Sexual Behavior, 2020)
Non-consensual sexual contact in bars is common, but few studies have focused on the extent of this problem at electronic dance music (EDM) parties, which are growing in popularity. We aimed to estimate prevalence and correlates of non-consensual sexual contact among individuals who attend EDM parties in New York City (NYC). Adults (ages 18–40 years) entering EDM parties in NYC were surveyed in 2018 using time–space sampling. Participants (n = 1005) were asked whether they had experienced unwanted or uninvited sexual contact including unwanted groping, kissing, or touching at an EDM party. We estimate that 15.2% of EDM party attendees in NYC have experienced non-consensual sexual contact at such parties. The majority (62.5%) of those reported that it occurred 1–2 times and 49.1% were usually or always drunk or high during the encounter(s). Almost all women experiencing non-consensual contact (99.5%) were all or mostly touched by men; 38.6% of men were all or mostly touched by other men. Women were at more than twice the odds of reporting non-consensual sexual contact than men (aOR = 2.38, p < .05) with 21.8% of women reporting experiencing non-consensual sexual contact compared to 11.0% of men. Among women, those ages 18–24 were at over twice the odds (aOR = 2.75, p < .05) of experiencing non-consensual sexual contact than those ages 25–40. EDM party environments can increase susceptibility to non-consensual sexual contact. Prevention needs to be geared toward those at risk, and education is needed for those likely to commit non-consensual sexual contact.
Keywords: Dance music; Drug use; Non-consensual sex; Sexual assault

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

“These things happen”: Hashtag activism and sexual harassment in the South African film and television industries - Paleker, Gairoonisa (Agenda, 2020)
In August 2017, the South African advocacy group Sisters Working in Film and Television (SWIFT) launched the #ThatsNotOk campaign, which has to date produced six episodes of short films (one episode in two parts, making it seven in total) elucidating the different forms sexual harassment takes, and the different scenarios in which it occurs, in the South African film and television industries. This profile engages with SWIFT and the Public Service Announcement (PSA) films as discursive sites and texts respectively, and provides textual analyses of the PSAs in the context of digital feminism and feminist activism against sexual harassment in the film and television industries. The profile motivates that as expressions of digital feminism, the PSAs critique the pervasiveness and normalisation of sexual harassment, while failing to engage with or critique the neoliberal logic and structure of the film and television industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10130950.2020.1720162
Keywords: #ThatsNotOk; Irina; South African film and television; digital feminism; hashtag activism

Unwanted Sexual Attention in the Night-Time Economy: Behaviors, Safety Strategies, and Conceptualizing “Feisty Femininity” - Gunby, Clare; Carline, Anna; Taylor, Stuart; Gosling, Helena (Feminist Criminology, 2020)
Almost nothing is known about ?unwanted sexual attention? and women?s navigation of it when in bars and nightclubs. Using focus group discussions, this article addresses that gap. It develops knowledge of the behaviors that constitute unwanted, the safety strategies used to manage them, and examines how these practices underpin gender performance in night-time spaces: environments renowned for the dilemmas they pose to women. We then use these data to develop the concept ?feisty femininity? to highlight a neglected form of femininity that overtly resists unwanted encounters. This femininity can arguably play a role in efforts aimed at ending gendered violence.
Publisher: SAGE Publications

‘Put some balls on that woman’: Gendered repertoires of inequality in screen composers’ careers - Cannizzo, Fabian; Strong, Catherine (Gender, Work & Organization, 2020)
This study contributes to debates about gendered career outcomes in the creative industries using data collected in interviews with Australian screen composers. We identify how gendered inequalities are legitimated through professional norms by comparing the responses of screen composers on barriers to women’s advancement. The article explores how three distinct interpretive repertoires help reproduce the gender inequality regime present in the screen composition field. These repertoires are ‘art vs. equality’, where working towards equality can be framed as antithetical to artistic ideals; ‘gendered music’, where men and women are posited as making fundamentally different types of music; and ‘confidence’, where men are framed as innately possessing certain entrepreneurial skills vital to success in the creative industries, while women both shoulder the blame for not possessing such skills and recognize the risks inherent for them in performing confidence. By focusing on repertoires, this study describes the means by which gender-based discrimination is made overt and offered justification among screen composers, posing challenges to organizations and individuals seeking to address gender inequality in the profession.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12496
Keywords: Australia; Musique de film; Myriam; composers; creative industries; cultural industries; gender inequality; sexism

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Sexual Harassment in the Post-Weinstein World - Grossman, Joanna L. (UC Irvine Law Review, 2020)
Keywords: Myriam; film industry

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Identity work in female-led creative businesses - Martin, Lynn; Jerrard, Bob; Wright, Lucy (Gender, Work & Organization, 2020)
This study explores the identity work carried out by three female owner-managers in creative industry businesses, identified in Government reports as a discriminatory industrial sector for women in the UK. Through the development of narratives by the owners and other participants, observation of practice and review of online and offline materials, three cases emerged. These showed overlapping, different identities developed and performed through identity work. Each presented rational and logical persona as business leaders despite observation showing extensive use of intuition and gut feeling in both creative and entrepreneurial aspects of the business. Intuition and gut feeling were seen as inappropriate at work as they belonged to the home sphere, emotionally based and therefore automatically unreliable. While occupying male stereotypes and avoiding the female realm of emotion at work, these women expressed femininity through their emphasis on the maternal, ‘being a good mother' as a desired ideal being embedded in work as well as home practice.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12357
Keywords: Myriam; creative industries; entrepreneurship; gender; identity; innovation

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Publisher: Johns Hopkins University Press
Keywords: Bibliographie; Nettoyer; Raphaël

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

The Changing Roles of Female Visual Artists in Morocco - El Azhar, Samir (Journal of Global Initiatives: Policy, Pedagogy, Perspective, 2019)
Keywords: Myriam

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Publisher: SAGE Publications Inc
Keywords: Bibliographie; Nettoyer

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - Gürkan, Hasan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Irina

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Bibliographie

Tackling gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, Sam (International Journal of Cultural Policy, 2019)
Cross-disciplinary research has highlighted the persistence of gender inequalities across music scenes. However, the way in which cultural policy shapes responses to gender inequalities in music has been relatively underexplored. This article draws on research from Swedish and UK contexts, supporting analysis with reference to 9 key-stakeholder interviews from both. Comparing perspectives from ‘more’ and ‘less’ gender-equal contexts, with sufficiently different cultural policy traditions, the article explores how responses to gender inequalities in music are influenced by ‘cultural democratic’ and ‘arm’s length’ approaches. It demonstrates that, as a result of these traditions, there is a comparatively more interventionist approach in Sweden at a national level, whereas the lack of central government response in the UK has encouraged more market-oriented solutions. It suggests that this ‘arm’s length’ approach necessitates different grassroots organisational strategies in order to affect change but notes that these, alongside austerity agendas, are insufficient in the long term.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2017.1341497
Keywords: Music policy; arm’s length; gender inequalities; interventionist; market-oriented

Sex Worker Resistance in the Neoliberal Creative City: An auto/ethnography - Tigchelaar, Alex (Anti-Trafficking Review, 2019)
Sex workers are subjects of intrigue in urban and creative economies. Tours of active, deteriorating, or defunct red-light districts draw thousands of tourists every year in multiple municipalities around the world. When cities celebrate significant anniversaries in their histories, local sex worker narratives are often included in arts-based public offerings. When sex workers take up urban space in their day-to-day lives, however, they are criminalised. Urban developers often view sex workers as existing serviceably only as legend. A history of sex work will add allure to an up-and-coming neighbourhood, lending purpose to its reformation into a more appropriately productive space, but the material presence of sex workers in these neighbourhoods is seen as a threat to community wellbeing and property values. This paper considers how sex workers, continuously displaced from environments they have carved out as workspaces, may use the arts to draw attention to these ongoing contradictions. It investigates how sex workers may make visible the idiosyncratic state of providing vitality to a city’s history while simultaneously being excluded from its living present. Most critically, it suggests ways in which sex workers may encourage those involved as producers and consumers of neoliberal urban revitalisation projects to connect these often fatal paradoxes to the laws that criminalise their labour.
Keywords: Bibliographie; Nettoyer

Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Number: 1 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate

Violence in the mosh pit: assault within the Australian punk scene - Barnes, Ash; White, Rob (Current Issues in Criminal Justice, 2019)
The mosh pit is a unique crowd formation where audience members dance aggressively to engage with the music, the performers and each other. However, in this space, Australian punks may experience violations of bodily integrity. Multiple levels and types of transgression occur, as members break with mosh pit ethics by engaging in unwanted and unlawful sexual and physical violence. This case study provides an example of how group normative behaviour is confounded in liminal spaces – how transgression within such spaces undermines the supposed freedom experienced by its participants. Whilst the mosh pit is perceived to be a site governed by its own particular ethics, some defy these in word and practice. The rules of engagement are ambiguous, and offenders are able to rationalise their harms through neutralisation techniques and the diffusion of blame and responsibility. The consequence is that more often than not, offenders can use the unique physical nature of the mosh pit to execute personal vendettas and engage in intentional violence such as ‘crowd killing’ and sexual assault, with little social and legal consequence. Moreover, a certain culture of denial permeates participant responses to these issues. Throughout it all, the violence occurring has a decidedly masculine basis, reflecting overarching gender differences in interpersonal violence generally.
Publisher: Routledge _eprint: https://doi.org/10.1080/10345329.2018.1556281
Keywords: assault; cultural criminology; denial; mosh pit; punk scene

Women composers’ use of online communities of practice to build and support their careers - Hennekam, Sophie; Macarthur, Sally; Bennett, Dawn; Hope, Cat; Goh, Talisha (Personnel Review, 2019)
Purpose The purpose of this paper is to examine women composers’ use of online communities of practice (CoP) to negotiate the traditionally masculine space of music composition while operating outside its hierarchical structures. Design/methodology/approach The authors employed a mixed methods approach consisting of an online survey (n=225) followed by 27 semi-structured in-depth interviews with female composers to explore the concept and use of CoP. Content analysis was used to analyze the survey responses and interpretative phenomenological analysis was used to interpret respondents’ lived experiences as relayed in the interviews. Findings The findings reveal that the online environment can be a supportive and safe space for female composers to connect with others and find support, feedback and mentorship, increase their visibility and develop career agency through learning and knowledge acquisition. CoP emerged as an alternative approach to career development for practicing female music workers and as a tool which could circumvent some of the enduring gendered challenges. Originality/value The findings suggest that online CoP can have a positive impact on the career development and sustainability of women in male-dominated sectors such as composition.
Publisher: Emerald Publishing Limited
Keywords: Career progression; Communities of practice; Creative industries; Gender; Mixed methodologies; Myriam; Women composers; music industry

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Publisher: Cambridge University Press
Keywords: Arts; Myriam; admiration; condonation; epistemic injustice; honor; silencing

The Role of Rape-Supportive Attitudes, Alcohol, and Sexual Arousal in Sexual (Mis)Perception: An Experimental Study - Benbouriche, Massil; Testé, Benoit; Guay, Jean-Pierre; Lavoie, Marc E. (Journal of Sex Research, 2019)
While sexual misperception does not irrevocably lead to sexual aggression, it remains a significant risk factor. The present study investigated the effects of rape-supportive attitudes, alcohol, and sexual arousal on sexual perception. We used a 2 × 2 between-participants factorial design to randomly assign 135 men from the general population to a condition with or without alcohol (blood alcohol concentration target of .08%) and to a condition with or without sexual arousal. Participants were asked to listen to an audiotape depicting a sexual interaction between a man and woman and to indicate if and when they believed the woman was no longer interested in having sex. Results, obtained through survival analyses, indicate that the effects of rape-supportive attitudes on sexual misperception are moderated by alcohol consumption. Alcohol appears to be an important situational factor for activating men's implicit theories. Our study sheds new light on the role of knowledge structures in sexual perception: It identifies when, as well as suggesting how, rape-supportive attitudes may disturb sexual perception and ultimately lead to sexual misperception.
Keywords: Adult; Alcohol Drinking; Arousal; Attitude; Female; Humans; Male; Rape; Refusal to Participate; Sexual Behavior; Survival Analysis; Tape Recording; Young Adult

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Experiences and perceptions of gender in the Australian music industry - Fairlamb, Hannah Mary; Fileborn, Bianca (Perfect Beat, 2019)
This article reports results from an online survey (n=207) about experiences and perceptions of gender from those working in the Australian music industry. Taking a feminist approach, theory on gender and hegemonic masculinity is used to discuss power in a gendered context in this industry. Literature shows women and girls experience a range of difficulties in the music industry worldwide, such as negative assumptions about their skill levels. The small body of research on gender and the Australian music industry has discussed topics such as the forgetting of women in Australian popular music history. Results reported in this article show that women’s worst experiences most often related to sexual violence or unwanted sexual advances; and men’s most often related to money. Findings contribute to the field by providing gendered analysis of self-reported data in an under-researched industry.
Keywords: Australia; gender; music; music industry; popular music; sexual harassment

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - G&#252, Hasan; rkan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Publisher: Scientia Kiadó
Keywords: Myriam; Turkey; film industry; gender; gender role; women

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Publisher: University of Toronto Press
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

#MeToo, Time's up, and Theories of Justice - Wexler, Lesley; Robbennolt, Jennifer K.; Murphy, Colleen (I) (University of Illinois Law Review, 2019)
Keywords: Irina

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Publisher: Intellect
Keywords: Irina

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Number: 1
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

What sexual harassment in Zentropa tells us about cultural policy post-Weinstein - Sorensen, Inge (Feminist Media Studies, 2018)
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2018.1456165
Keywords: Irina

A Dance with Many Secrets: The Experience of Emotional Harm from the Perspective of Past Professional Female Ballet Dancers in Canada - Moola, Fiona; Krahn, Alixandra (Journal of Aggression, Maltreatment & Trauma, 2018)
Originating in the Italian and French courts, ballet is an age-old art that fuses aesthetics and athleticism (Wulff, 2008). Despite changing times, ballet masters and mistresses tenaciously hold on to a sense of deep traditionalism. However, some scholars suggest that unwavering devotion to the art may conceal troubled embodied relations and oppressive practices (Gvion, 2008). In this study, we drew on the phenomenological research tradition in an effort to further examine the power relations that play out on the body in the world of Canadian professional ballet (Papaefstathiou, Rhind, & Brakenridge, 2013). Twenty past professional female ballet dancers from across Canada participated in this study. Our dedicated dancers were relentless. They sacrificed body and mind in the pursuit of excellence in a broader cultural context that expected nothing less. The dancers normalized harmful emotional experiences, inappropriate sexual transgressions, and chronic injury (Gvion, 2008). They also described experiences of neglect—and feeling replaceable—after the onset of injury. We have attempted to theorize our findings within the context of embodiment literature and the work of gender theorists. Emboldened by our dancers’ voices, we have shed light—and broken secrets—regarding some of the harmful practices that still characterize professional ballet in Canada. We hope that our work might further continue efforts to democratize power imbalances in professional ballet and ultimately enhance holistic dancer development and health.
Publisher: Routledge _eprint: https://doi.org/10.1080/10926771.2017.1410747

“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

EDM and Ecstasy: the lived experiences of electronic dance music festival attendees - Little, Noah; Burger, Birgitta; Croucher, Stephen M. (Journal of New Music Research, 2018)
Attendance at large-scale music festivals has captivated a global interest in these spectacular experiences, yet little is known about the lasting benefits and personal changes individuals incur following this event. This study aims to provide a comprehensive exploration of the lived experiences of individuals who attended a multi-day electronic dance music festival. The present study was primarily interested in the perceived beneficial changes within the individual, following their festival experience. We investigated if first-time festival attendees perceived changes differed to those of returning individuals. Semi-structured qualitative interviews were used to collect data from 12 individuals who attended the 2015 Electronic Daisy Carnival in Las Vegas. Six participants were first-time attendees while the remaining six were individuals returning to the festival. The data was analysed using Thematic Analysis. Within the data emerged the following central themes: (1) escape, (2) communitas, and (3) self-reported changes; there were 10 subthemes. These findings add to the existing body of music festival literature, further contextualizing how music festivals are both experienced, and reflected upon by individuals. Further, this study highlights the potential lasting changes individuals’ experience from attending electronic dance music festivals.
Publisher: Routledge _eprint: https://doi.org/10.1080/09298215.2017.1358286
Keywords: Music festival; electronic dance music; music; social acceptance; social cohesion

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Publisher: Cahiers de théâtre Jeu inc.
Keywords: Bibliographie; Nettoyer

The Right of One's Own Image in the Recent Cases of Sexual Harassment in Film Industry: Applying the European Theory of Concentric Circles to Celebrities (In Particular, Women) - Corredoira, Loreto (Journal of Information Policy, 2018)
Keywords: Irina

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Publisher: 6876
Keywords: Bibliographie; Nettoyer

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Toby, Bennett (Gender Politics in the Music Industry, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.

L’ordinaire de la violence. Un cas d’atteinte sexuelle sur mineure en milieu artistique - Trachman, Mathieu (Travail, genre et sociétés, 2018)
L’ordinaire est un thème souvent mobilisé dans les études sur les violences de genre. À partir d’un cas d’atteinte sexuelle sur mineure, cet article a pour objectif d’en préciser les enjeux. Il montre en premier lieu que la notion d’ordinaire, qui signifie souvent ce qui est commun à toutes les femmes, gagne à voir son périmètre précisé : dans le cas analysé, le travail artistique, sa dimension vocationnelle, la personnalisation des relations entre professeur et étudiante, les coûts d’entrée dans le métier pour les femmes sont des éléments déterminants. Dans les études féministes, l’ordinaire désigne également les faits de violence qui caractérisent la vie quotidienne des femmes. En distinguant faits, situation et qualification, l’article montre que la qualification de violence implique un sentiment d’anormalité et une réflexivité largement absents dans les situations de violence de genre. Ce hiatus explique l’incertitude souvent inhérente à la qualification de violence et le caractère rétrospectivement énigmatique des situations de violence. L’ordinaire de la violence désigne ainsi moins une évidence occultée qu’un registre de l’expérience où les abus et les agressions sont intégrés dans le cours des choses et normalisés par les protagonistes.
Place: Paris Publisher: La Découverte

Dick pics on blast: A woman’s resistance to online sexual harassment using humour, art and Instagram - Vitis, Laura; Gilmour, Fairleigh (Crime, Media, Culture, 2017)
This article brings to attention and explores women?s use of non-traditional forms of resistance to online sexual harassment. In this piece we use Anna Gensler?s Instagram art project Instagranniepants to examine how women are appropriating the language and practices of the cyber realm to expose online sexual harassment and to engender a creative resistance which is critical, comedic and entertaining. Drawing from interdisciplinary literature on witnessing, satire and shaming, we explore the techniques Gensler uses to not only document harassment but also resist, engage and punish those who seek to perpetrate it. This article problematises the stereotype of women as passive victims of online public spaces, and is critical of popular discourses that portray online spaces as exclusively risky and that position women as the natural victims of online violence. It concludes that a more nuanced account of women?s negotiation of online spaces is necessary, particularly as an overarching narrative of risk and victimisation undermines the liberatory potential of the online realm.
Publisher: SAGE Publications
Keywords: Myriam; Résistance aux VACS

Forty-Seven DJs, Four Women: Meritocracy, Talent, and Postfeminist Politics - Gadir, Tami (Dancecult, 2017)
In 2016, only four of forty-seven DJs booked for Musikkfest, a festival in Oslo, Norway, were women. Following this, a local DJ published an objection to this imbalance in a local arts and entertainment magazine. Her editorial provoked booking agents to defend their position on the grounds that they prioritise skill and talent when booking DJs, and by implication, that they do not prioritise equality. The booking agents’ responses, on social media and in interviews I conducted, highlight their perpetuation of a status quo in dance music cultures where men disproportionately dominate the role of DJing. Labour laws do not align with this cultural attitude: gender equality legislation in Norway’s recent history contrasts the postfeminist attitudes expressed by dance music’s cultural intermediaries such as DJs and booking agents. The Musikkfest case ultimately shows that gender politics in dance music cultures do not necessarily correspond to dance music’s historical associations with egalitarianism.

Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

When Women Do Not Want It: Young Female Bargoers’ Experiences With and Responses to Sexual Harassment in Social Drinking Contexts - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha (Violence Against Women, 2017)
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women?s responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends? help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.
Publisher: SAGE Publications Inc

Data and responsibility: Towards a feminist methodology for producing historical data on women in the contemporary UK film industry - Cobb, Shelley; Wreyford, Natalie (Feminist Media Histories, 2017)
This paper addresses how feminist interrogations of research methods and knowledge claims have an important role to play in the collection and dispersion of quantitative data. Taking the contemporary film industry as a historical formation, and seeking to identify and understand patterns of continued gendered inequality, we consider the methodological and ethical dilemmas we have experienced as feminist researchers gathering and presenting quantitative data on the numbers of women working in the UK film industry between 2003 and 2015. We argue that data plays a paradoxical role in creating a sense of women’s absence and arrive at a set of guiding principles for feminist quantitative research in film histories.
Number: 3

Indian women journalists' responses to sexism and sexual harassment - Chadha, Kalyani; Steiner, Linda; Guha, Pallavi (International Communication Research Journal, 2017)
Gale Academic OneFile includes Indian women journalists' responses to sexism and by Kalyani Chadha, Linda Steiner, and Pall. Click to explore.
Publisher: International Communication Division (ICD), of AEJMC
Keywords: Myriam; journalism

The deterrent effects of Australian street-level drug law enforcement on illicit drug offending at outdoor music festivals - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne; Ritter, Alison; Weatherburn, Don; MacCoun, Robert (International Journal of Drug Policy, 2017)
Background Australian and international street-level drug law enforcement deploy many strategies in efforts to prevent or deter illicit drug offending. Limited evidence of deterrence exists. This study assessed the likely impacts of four Australian policing strategies on the incidence and nature of drug use and supply at a common policing target: outdoor music festivals. Methods A purpose-built national online survey (the Drug Policing Survey) was constructed using five hypothetical experimental vignettes that took into account four policing strategies (High Visibility Policing, Riot Policing, Collaborative Policing, and policing with Drug Detection Dogs) and a counter-factual (no police presence). The survey was administered in late 2015 to 2115 people who regularly attend festivals. Participants were block-randomised to receive two vignettes and asked under each whether they would use, possess, purchase, give or sell illicit drugs. Results Compared to ‘no police presence’, any police presence led to a 4.6% point reduction in engagement in overall illicit drug offending: reducing in particular willingness to possess or carry drugs into a festival. However, it had minimal or counterproductive impacts on purchasing and supply. For example, given police presence, purchasing of drugs increased significantly within festival grounds. Offending impacts varied between the four policing strategies: Drug Detection Dogs most reduced drug possession but High Visibility Policing most reduced overall drug offending including supply. Multivariate logistic regression showed police presence was not the most significant predictor of offending decisions at festivals. ConclusionConclusion The findings suggest that street-level policing may deter some forms of drug offending at music festivals, but that most impacts will be small. Moreover, it may encourage some perverse impacts such as drug consumers opting to buy drugs within festival grounds rather than carry in their own. We use our findings to highlight trade-offs between the goals of public health promotion and crime control in street-level enforcement.
Keywords: Deterrence; Drug law enforcement; Supply; Use

Rape culture, lad culture and everyday sexism: researching, conceptualizing and politicizing new mediations of gender and sexual violence - Phipps, Alison; Ringrose, Jessica; Renold, Emma; Jackson, Carolyn (Journal of Gender Studies, 2017)
Introduction to Special Issue of Journal of Gender Studies entitled Rape culture, lad culture and everyday sexism: Researching, conceptualizing and politicizing new mediations of gender and sexual violence.

Skipping a beat: Assessing the state of gender equality in the Australian music industry - Cooper, Rae; Coles, Amanda; Hanna-Osborne, Sally (2017)
This report demonstrates that male advantage is a pervasive feature of the Australian music industry. Using publicly available published data the report interrogates the industry dynamics that have produced a contemporary music scene in which radio playlists, festival line-ups, industry awards, peak bodies and major industry boards are dominated by male contributions and voices. We make 5 key recommendations, discussed in more detail in the report, to begin the process of addressing the industry’s chronic gender inequality: 1. Collect more and better data on the music industry on a gender disaggregated basis; 2. Establish a well-resourced independent gender equality industry advocacy body; 3. Use gender equality criteria in deciding public funding outcomes; 4. Increase women’s representation in decision-making structures; 5. Address gender bias in the Australian music industry by prioritising inclusivity and representation as core industry values (for example through funding and implementing training programs). The music industry is skipping a beat when it comes to gender equality. We hope that our report will stimulate industry thinking and action for change.
Accepted: 2019-10-24 Publisher: University of Sydney

The Going Out In Sydney App: Evaluating the Utility of a Smartphone App for Monitoring Real-World Illicit Drug Use and Police Encounters Among Festival and Club Goers - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne Louisa (Substance Abuse: Research and Treatment, 2017)
Gaining accurate information on illicit drug use and policing in real-world settings is a challenge. This study examines the utility of a smartphone app (‘Going Out In Sydney’) to prospectively follow up illicit drug use and policing encounters at music festivals and licensed entertainment precincts in Sydney, Australia. In all, 38 regular festival and licensed entertainment venue attendees used the app to log nights out over a 3-month period, including (1) where they went (eg, festival, nightclub), (2) the prevalence of illicit drug use, and (3) the incidence and nature of police encounters. A survey and interview were then conducted about the utility of the app. The app enabled rich data collection (n = 353 entries) about illicit drug use and policing at both target settings. Follow-up surveys indicated that most participants were extremely satisfied with the ease of use of the app and privacy afforded, and compared with other data collection modes, such as paper-based logs and online surveys, rated the app the most desirable method of data collection. This suggests smartphone apps may be a viable option for future studies on illicit drug use and policing of drugs.
Publisher: SAGE Publications Ltd STM
Keywords: Mobile app; app; drug use; offending; policing; smartphone

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
This article contextualizes some of the roles that women played in Montreal’s interwar jazz scene. The archives testify to the importance of pianists such as Vera Guilaroff and Ilene Bourne, piano teacher Daisy Peterson Sweeney, dance teachers Olga Spencer Foderingham and Ethel Bruneau, as well as black women performers on the variety stage in the development of Canada’s most thriving jazz scene in the first half of the twentieth century. This article explains why women were drawn to these particular performance spaces (piano, teaching, theatrical dance) and documents the historiographical processes that have led to their marginalization from the historical record.
Publisher: Société québécoise de recherche en musique
Keywords: Bibliographie; Nettoyer

gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, S (International Journal of Cultural Policy, 2017)

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments' policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands' creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors influenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-specific research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12176

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Publisher: Routledge _eprint: https://doi.org/10.1080/10632921.2016.1231645
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概

LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden (Museums & Social Issues, 2016)
Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM’s 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com).
Publisher: Routledge _eprint: https://doi.org/10.1080/15596893.2016.1217460
Keywords: Bibliographie; Coffre à outils; Lesbian; Nettoyer; bisexual; diversity; gay; inclusion; transgender

Drugs at the campsite: Socio-spatial relations and drug use at music festivals - Dilkes-Frayne, Ella (International Journal of Drug Policy, 2016)
Background Music festivals have received relatively little research attention despite being key sites for alcohol and drug use among young people internationally. Research into music festivals and the social contexts of drug use more generally, has tended to focus on social and cultural processes without sufficient regard for the mediating role of space and spatial processes. Methods Adopting a relational approach to space and the social, from Actor-Network Theory and human geography, I examine how socio-spatial relations are generated in campsites at multiple-day music festivals. The data are drawn from ethnographic observations at music festivals around Melbourne, Australia; interviews with 18–23 year olds; and participant-written diaries. Results Through the analysis, the campsite is revealed as a space in process, the making of which is bound up in how drug use unfolds. Campsite relations mediate the formation of drug knowledge and norms, informal harm reduction practices, access to and exchange of drugs, and rest and recovery following drug use. Conclusions Greater attendance to socio-spatial relations affords new insights regarding how festival spaces and their social effects are generated, and how they give rise to particular drug use practices. These findings also point to how festival harm reduction strategies might be enhanced through the promotion of enabling socio-spatial relations.
Keywords: Drug use; Enabling places; Ethnography; Music festivals; Social context; Socio-spatial relations

Post-postfeminism? New feminist visibilities in postfeminist times - Gill, R. (Feminist Media Studies, 2016)
This article contributes to debates about the value and utility of the notion of postfeminism for a seemingly “new” moment marked by a resurgence of interest in feminism in the media and among young women. The paper reviews current understandings of postfeminism and criticisms of the term’s failure to speak to or connect with contemporary feminism. It offers a defence of the continued importance of a critical notion of postfeminism, used as an analytical category to capture a distinctive contradictory-but-patterned sensibility intimately connected to neoliberalism. The paper raises questions about the meaning of the apparent new visibility of feminism and highlights the multiplicity of different feminisms currently circulating in mainstream media culture – which exist in tension with each other. I argue for the importance of being able to “think together” the rise of popular feminism alongside and in tandem with intensified misogyny. I further show how a postfeminist sensibility informs even those media productions that ostensibly celebrate the new feminism. Ultimately, the paper argues that claims that we have moved “beyond” postfeminism are (sadly) premature, and the notion still has much to offer feminist cultural critics.
Number: 4

Cultural value and cultural policy: some evidence from the world of live music - Behr, Adam; Brennan, Matt; Cloonan, Martin (International Journal of Cultural Policy, 2016)
This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen’s Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2014.987668
Keywords: audience research; cultural value; live music; music policy; regulation

Taking time between g-string changes to educate ourselves: Sinéad O’Connor, Miley Cyrus, and celebrity feminism - Brady, Anita (Feminist Media Studies, 2016)
This article examines the feminist response to a 2013 online “feud” between singers Miley Cyrus and Sinéad O’Connor that began when Cyrus connected the video for her single “Wrecking Ball” to O’Connor’s video for “Nothing Compares 2 U.” O’Connor’s response criticised Cyrus’ sexualised image, and the exchanges that followed sparked debate among feminists over the limits of sexual “agency,” and the sexual politics of feminism. This took place within a wider media context that has seen an apparent increase in female celebrities explicitly identifying themselves as feminist. Critics of this “celebrity feminism” argue that the sexualised star systems of its proponents are at odds with the aims of feminist politics. This article draws on post-structuralist feminist theory to question the positioning of celebrity feminism as exterior to an imagined “feminist movement.” Using the Cyrus/O’Connor feud, I argue that such a binary potentially reaffirms the structures of power that feminism seeks to oppose, and ignores the ways celebrity culture and contemporary media practice might combine to produce new understandings of the field of feminism.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1137960
Keywords: Celebrity feminism; Miley Cyrus; Sinéad O’Connor; feminist post-structuralism; third-wave feminism

Damaging and daunting: female journalists’ experiences of sexual harassment in the newsroom - North, Louise (Feminist Media Studies, 2016)
Female journalists’ experiences of sexual harassment are barely documented in the literature about Australian news journalism despite evidence of its ongoing prevalence. There have been some stories of harassment detailed in autobiographies by female journalists and the occasional article in the mainstream media about individual incidents, but it wasn’t until 1996 that a union survey provided statistical evidence of an industry-wide problem. That Media, Entertainment and Arts Alliance survey found that more than half of the 368 female participants had experienced sexual harassment at work. In 2012, I conducted the largest survey of female journalists in Australia finding that there was an increased number of respondents who had experienced sexual harassment in their workplaces. In a bid to better understand female journalists’ experiences of sexual harassment, this paper analyses written comments made by survey participants in relation to key questions about harassment. It finds that most downplay its seriousness and do not make formal reports because they fear victimisation or retaliation. As a consequence, a culture of secrecy hides a major industry problem where many women believe they should work it out themselves and that harassment is the price they have to pay for working in a male-dominated industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1105275
Keywords: Myriam; Sexual harassment; female journalists; gender and work; gendered newsrooms; survey of Australian female journalists

Women Harassment at Workplace: A Study of Pakistani Television Channels - Zia, Anjum; Batool, Sumera; Yasin, Zaeem (2016)
The present study explores the contemporary status of women harassment in Pakistani media industry taking alongside theoretical consideration of liberal feminism theory. An empirical method was adopted and in-depth interviews were conducted with media employees of both genders at television channels of the country. The study examined six core dimensions of harassment including working environment of the organization, male dominance, women harassment at workplaces, stereotype thinking patterns about women, offensive remarks on appearance of female colleagues and reporting of harassment issues to explore the current situation of women harassment in television channels of high repute. Findings of the study revealed that regardless of their ample role in thriving Pakistani media, women journalists are facing harassment at their workplaces but majority of them lesser likely to report harassment issues. Existence of stereotype thinking patterns about women and offensive remarks about appearance of women point towards severity of situation about women harassment at Pakistani media industry. Interestingly, despite male domination in media industry, general environment of media organizations is reported as satisfactory at large, whereas research concludes with highlighting areas for people working within and outside media organizations to eradicate harassment at workplaces. Keywords: Women harassment, male dominance, stereotype thinking patterns, Pakistani media, reporting of harassment.
Keywords: Myriam; Television

Learning to labour unequally: Understanding the relationship between cultural production, cultural consumption and inequality - Oakley, Kate; O'Brien, Dave (Social Identities, 2016)
Inequality has become essential to understanding contemporary society and is at the forefront of media, political and practice discussions of the future of the arts, particularly in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The article considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The paper argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy, despite the importance of culture to British and thus international policy agendas. The article uses the example of higher education in the UK to think through the relationship between cultural consumption and production. In doing, so the article maps out a productive possibility for a new research agenda, by sketching where and how research might link cultural consumption and production to better understand inequality.

Navigating the boys’ club: Debra DiGiovanni and the performative strategy of comic self-deprecation - Deveau, Danielle Jeanine (International Journal of Cultural Studies, 2016)
This article considers Canadian comedian Debra DiGiovanni’s self-deprecatory humour as a performative strategy. In keeping with a performance tradition of self-deprecation as established by women like Phyllis Diller and Joan Rivers, DiGiovanni offers ‘failure’ as a comic strategy. Her comedy is heavily reliant upon the framing of her lack in relationships, in self-control and in body image (in relation to normative gender standards and expectations). At the same time, however, DiGiovanni also engages critically with gendered expectations of heteronormative desirability, lampooning thin women, superficial men and celebrity culture. Although her comedy is generally characterized by self-deprecation, her humour also leaves space for an ambivalent politics of gender.
Keywords: Sophie-Anne

"Yeah, We Serve Alcohol, but … We Are Here to Help": A Qualitative Analysis of Bar Staff's Perceptions of Sexual Violence - Powers, Ráchael A.; Leili, Jennifer (Violence and Victims, 2016)
This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provider, their lack of knowledge (but eagerness to learn), and their reliance on stereotypical scenarios of sexual violence and interventions. These findings are situated in a framework for understanding barriers to bystander intervention and implications for community-based bystander programs are discussed.
Keywords: Adult; Camille; Female; Focus Groups; Helping Behavior; Humans; Interpersonal Relations; Male; Rape; Restaurants; Sex Offenses

‘Safe Spaces’: Experiences of Feminist Women-Only Space - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon (Sociological Research Online, 2015)
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of ‘safe space’ are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of ‘safety’ for women and, particularly, the meaning and experience of spaces they consider to be ‘safe.’ Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as ‘safe space’ to explore the significance and meaning of ‘safety’ in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being ‘safe to’ denotes fundamental aspects of civic engagement, personhood and freedom.
Publisher: SAGE Publications Ltd
Keywords: Activism; Feminism; Safety; Space; Women; Women-Only

All the girls in town: The missing women of Australian rock, cultural memory and coverage of the death of Chrissy Amphlett - Strong, Catherine (Perfect Beat, 2015)
This article will use the cultural and media materials produced around the death of Chrissy Amphlett as a way of interrogating the fact that surprisingly few resources exist that document or commemorate the contribution of women to the rock music scene in Australia. As Amphlett is unusual in being a woman who has, even before her death, claimed a place in the Australian rock canon, examining materials that are designed to construct her legacy upon her passing will provide examples of how women in Australian rock are discussed. It will be demonstrated that Amphlett’s gender is central to these discussions, and that she is used to both obscure the contributions of other women performers and to deny a need for women musicians to even be an object of discussion at all. These indings will be analysed using Aleida Assmann’s concepts of functional and storage memory, and it will be argued that the lack of information that we have about past female rockers makes it harder for women in Australia to see this ield as one they can participate in, and also makes the retention of memories about currently successful women musicians less likely.

Pathways to Help: Adolescent Sexual Assault Victims’ Disclosure and Help-Seeking Experiences - Campbell, Rebecca; Greeson, Megan R.; Fehler-Cabral, Giannina; Kennedy, Angie C. (Violence Against Women, 2015)
In this study, we conducted semistructured interviews with N = 20 adolescent sexual assault victims who sought postassault help from the medical and legal system to understand young survivors’ disclosure and help-seeking processes. Results revealed three distinct disclosure patterns and pathways to help-seeking. First, in the voluntary disclosure group, victims told their friends, who encouraged them to tell an adult, who then encouraged—and assisted—the survivors in seeking help. Throughout this process, the survivors’ disclosures at each step were within their control and reflected their choices for how to proceed. Second, in the involuntary disclosure pattern, victims also first disclosed to friends, but then those friends told adults about the assault, against the survivors’ wishes; the adults made the victims seek help, which was also against the survivors’ preferences. Third, in situational disclosures, the survivors were unconscious at the time of the assault, and their friends disclosed and sought help on their behalf. We also examined how these initial disclosure patterns related to victims’ continued engagement with these systems.
Publisher: SAGE Publications Inc
Keywords: adolescents; disclosure; help-seeking; rape; sexual assault

‘I Think Women are Possibly Judged More Harshly with Comedy’: Women and British Television Comedy Production - Mills, Brett; Ralph, Sarah (Critical Studies in Television, 2015)
Critics and creative workers have recently highlighted the lack of women working in British television comedy. Through thematic analysis of interviews with British television comedy professionals, this article explores how women talk about their work and their position within the industry. Outlining the specific industrial contexts within which female comedy professionals work, the article examines institutionalised gender norms and practical impediments which the interviewees' responses reveal, while also exploring the institutional and personal initiatives which they have developed to address these problems.
Publisher: SAGE Publications

Cultural Value and Inequality: A Critical Literature Review - Oakley, K; O'Brien, D (2015)
Inequality has become essential to understanding contemporary British society and is at the forefront of media, political and practice discussions of the future of the arts in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The literature review considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The review argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy. The review concentrates on the ‘big three’ issues of inequality – race, class and gender, where most of the literature is to be found, but also touches on disability, sexuality and spatial inequality. All of the research reviewed suggests an undeniable connection between cultural value and inequality. Understanding that connection is currently impeded by problems with data. The report suggests the political saliency of this topic means that public policy must do more to provide robust research, particularly about cultural production.

Sex, Gender and Work Segregation in the Cultural Industries - Hesmondhalgh, David; Baker, Sarah (The Sociological Review, 2015)
This chapter addresses work ‘segregation’ by sex in the cultural industries. We outline some of the main forms this takes, according to our observations: the high presence of women in marketing and public relations roles; the high numbers of women in production co-ordination and similar roles; the domination of men of more prestigious creative roles; and the domination by men of technical jobs. We then turn to explanation: what gender dynamics drive such patterns of work segregation according to sex? Drawing on interviews, we claim that the following stereotypes or prevailing discourses, concerning the distinctive attributes of women and men, may influence such segregation: that women are more caring, supportive and nurturing; that women are better communicators; that women are ‘better organized’; and that men are more creative because they are less bound by rules.
Publisher: SAGE Publications Ltd
Keywords: cultural industries; sexual division of labour; stereotypes; work segregation

The Economic and Cultural Value of Live Music in Australia 2014 - Carter, D. (2015)
The Economic and Cultural Value of Live Music in Australia 2014

Gender and creative labour - Conor, B; Gill, R; Taylor S (The Sociological Review, 2015)
Keywords: gender inequality; neoliberalism; precariousness; self-representation; sexism

Unspeakable Inequalities: Post Feminism, Entrepreneurial Subjectivity, and the Repudiation of Sexism among Cultural Workers - Gill, Rosalind (Social Politics: International Studies in Gender, State & Society, 2014)
Work in the cultural and creative fields is marked by stark and growing inequalities relating to gender, class, and race/ethnicity. Yet, the same industries are also characterised by an ethos that celebrates openness, egalitarianism, and meritocracy. This paper explores this paradox, focusing in particular on gender inequalities. It argues that there is a need to move beyond the standard conventional explanations for women's under-representation within the creative workforce, which point to female childbearing and childcare as central. Whilst not disputing the significance of motherhood to women's career trajectories, the paper suggests that the repeated focus on maternity is problematic and may close down other areas of potential investigation and critique. The paper suggests that three alternative foci would repay attention in understanding inequalities in the CCI. First, the new, mobile, subtle, and revitalised forms of sexism in circulation urgently require further examination. Secondly, the power of the dominant post feminist sensibility which, in suggesting that “all the battles have been won,” renders inequality increasingly difficult to voice or speak about, demands critique. Thirdly, the new forms of labouring subjectivity required to survive in the field of cultural work may themselves be contributing to the inequalities in the field, by favouring an entrepreneurial individualistic mode that disavows structural power relations. These three aspects of life in the field of cultural work merit further attention and suggest that gender inequality has a variety of different causes, not all located in women's childbearing abilities. Moreover, the paper argues that the very myth of egalitarianism at work in the CCI may itself be a key mechanism through which inequality is reproduced.

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Fortunes of feminism: from state-managed capitalism to neoliberal crisis - Guest, Carly (European Journal of Cultural and Political Sociology, 2014)
Publisher: Routledge _eprint: https://doi.org/10.1080/23254823.2014.948028

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10304312.2014.888040
Keywords: Bibliographie; Irina; Nettoyer

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence

Safe Space: Towards a Reconceptualization (Antipode, 2014)
The term “safe space” dates to the late twentieth century women's movement, but it has since been used in many different contexts. In this paper, we review and analyze historical and contemporary “safe spaces”. These include “separatist” safe spaces in women's, anti-racist, and feminist communities, “inclusive” safe space classrooms, and safe spaces in which (non-human) objects are central. We argue that safe spaces should be understood not through static and acontextual notions of “safe” or “unsafe”, but rather through the relational work of cultivating them. Such an understanding reveals several tendencies. Namely, safe spaces are inherently paradoxical. Cultivating them includes foregrounding social differences and binaries (safe–unsafe, inclusive–exclusive) as well as recognizing the porosity of such binaries. Renegotiating these binaries is necessarily incomplete; a safe space is never completely safe. Even so, we encourage the critical cultivation of safe space as a site for negotiating difference and challenging oppression.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/anti.12089
Keywords: activism; intersectionality; paradoxical space; porosity; safe space; safety

A Music Room of One's Own: Discursive Constructions of Girls-only Spaces for Learning Popular Music - Björck, Cecilia (Girlhood Studies, 2013)
This article elaborates on discursive constructions of girls-only settings through the spatial metaphor of a room of one's own, as articulated in round-table discussions among staff and participants from girl-centered music programs in Sweden. The idea of a separate room refers to spaces for collective female empowerment as well as for individual knowledge acquisition and creativity. These spaces are constructed so as to provide the possibility for exploration, subjectivity, and focus, by offering (partial and temporary) escape from competition and control, from a gendered and gendering gaze, and from distraction. Girl-centered programs are also discussed as paradoxical because they function as gender-neutral when seen from the inside, but gender-specific when seen from the outside.
Publisher: Berghahn Journals Section: Girlhood Studies

From victim to survivor - and from survivor to victim: Reconceptualising the survivor journey - Jordan, Jan (Sexual Abuse in Australia and New Zealand, 2013)
Being recognized as a rape survivor has often been interpreted as implying a linear progression from the negative state of victimisation, experienced in the presence of the offender, to a stronger, more positive state, typically facilitated by external support mechanisms. Drawing primarily on interviews conducted with women victimised by New Zealand serial rapist, Malcolm Rewa, this article challenges the concept of a journey 'from victim to survivor' by considering the multiple ways in which these women sought to protect themselves and survive during the attack while also experiencing aspects of their postattack involvement with individuals and agencies as further victimisation. The article concludes by outlining some initial implications regarding what this may mean for professionals working with victim/survivors of sexual violence.
Publisher: Australian and New Zealand Association for the Treatment of Sexual Abuse
Keywords: Bibliographie; Nettoyer

Safe Space: The Riot Grrrl Collection - Keenan, Elizabeth K.; Darms, Lisa (Archivaria, 2013)
Riot Grrrl, an early-1990s teen feminist movement, adopted punk’s DIY modes of expression to encourage girls to address their shared oppression. The Riot Grrrl Collection, held at New York University’s Fales Library & Special Collections, documents the movement through the personal papers of those who were active in its formative years. This article uses the lens of feminist “safe space” to look at the collection from two perspectives: that of its founder, Lisa Darms, who is senior archivist at Fales, and that of ethnomusicologist Elizabeth Keenan, a scholar who has worked extensively with the collection. The concept of safe space was crucial to the all-girl meetings, dance parties, and bands that formed the foundation of Riot Grrrl. The authors argue that the safe space of Riot Grrrl created an intimate counter-public – that is, a space where girls established a feminist community through shared texts – but one that sometimes worked against its own intentions: boundaries erected for safety sometimes led to exclusion along lines of race, class, or gender identity. The authors extend the idea of safe space to issues of collection building from and within activist communities; to ideas of intimacy and privacy as they play out for donors, for researchers, and in the special collections reading room; and to the tension between the desire for access to activist history versus the requirements of archival preservation. The article examines how iterations of safe space are enacted across the personal papers in the Riot Grrrl archive, through both the materials themselves and their place in the archive. RÉSUMÉ Riot Grrrl, un mouvement du début des années 1990 pour adolescentes féministes, s’est inspiré du mouvement punk pour adopter les modes d’expression du « Do it yourself (DIY) », dans le but d’encourager les adolescentes à aborder leur oppression commune. La collection Riot Grrrl, détenue par la Fales Library & Special Collections de l’University New York, documente le mouvement grâce aux documents personnels de celles qui en étaient actives durant ses premières années. Cet article se sert du concept féministe du « lieu sûr » (« safe space ») afin d’examiner la collection à partir de deux perspectives : celle de sa fondatrice, Lisa Darms, qui est archiviste supérieure à Fales, et celle de l’ethnomusicologue Elizabeth Keenan, une spécialiste qui a travaillé en profondeur avec cette collection. Le concept du lieu sûr était crucial pour les adolescentes lors de leurs réunions et soirées dansantes et pour leurs groupes musicaux qui ensemble ont contribué à la fondation de Riot Grrrl. Les auteurs soutiennent que le lieu sûr de Riot Grrrl a créé un « contre-public intime » – c’est-à-dire un espace dans lequel les adolescentes ont pu établir une communauté féministe par l’entremise de textes partagés – mais un contre-public qui opérait parfois contre ses propres intentions : les limites imposées pour délimiter le lieu sûr ont parfois mené vers des exclusions basées sur la race, les classes sociales ou l’identité de genre. Les auteures élargissent le concept du lieu sûr aux questions liées à la création de collections par des communautés militantes et dans ces milieux; aux idées de l’intimité et de la vie privée auxquelles sont confrontés les donateurs et les chercheurs dans la salle de lecture des collections spéciales; et à la tension entre le désir d’avoir accès à l’histoire militante et les besoins liés à la conservation archivistique. Cet article examine comment l’itération du lieu sûr se fait par rapport aux documents personnels des archives Riot Grrrl, tant du côté des documents eux-mêmes que de leur place dans les archives.

Female, Mosher, Transgressor: A 'Moshography' of Transgressive Practices within the Leeds Extreme Metal Scene - Riches, Gabrielle; Lashua, Brett; Spracklen, Karl (IASPM Journal, 2013)
This paper examines and reconceptualises transgression in the Leeds extreme metal music subculture through theories of performance, embodiment and spectacle. The spectacle, for Debord (1967), is a social relation that is alienating and mediated by images, visuals, and technology. At a live extreme metal concert fans subvert social norms, challenge gendered expectations, and disregard norms of etiquette and decency. Moshing is the most visible and sensuous example of transgression within the extreme metal scene. It is an aggressive, physically demanding performance which embodies resistance to the impersonal and disillusioning world of the spectacle (Halnon, 2004). The pit is a transgressive space that is itself transgressed by women who participate in this masculine, chaotic space, disrupting the homosocial bonds of male solidarity (Gruzelier, 2007). This paper offers an ethnographic account of a female metal fan participating in the transgressive practice of moshing within the Leeds metal music scene – a moshography.
Number: 1
Keywords: Moshpits; embodiment; extreme metal music; performance ethnography; spectacle; transgression

Why producers of music use discourses of consumption (and why we shouldn't think that makes them prosumers) - Cluley, Robert (Arts Marketing: An International Journal, 2013)
Purpose ‐ The purpose of this paper is to demonstrate how people making music represent their production activities using images of consumption. Design/methodology/approach ‐ Supporting evidence is based on in-depth interviews with musicians and support personnel. The data are structured through a thematic analysis. Findings ‐ The paper argues that consumption serves as a discursive resource that allows cultural producers to make sense of production activities which do not conform to an image of production as an alienated form of labour. Originality/value ‐ Relating the analysis to the ongoing attempts to conceptualise cultural producers through the concept of prosumption, the paper concludes that there are limits to cultural producers' abilities to represent their production activities as production rather than a structural change in social or economic organisation, as suggested by some consumer researchers.

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

Looking for Something New: The Provision of Popular Music Studies Degrees in the UK - Cloonan, Martin; Hulstedt, Lauren (IASPM Journal, 2013)
This article reports the findings of some commissioned research, which was conducted by the authors in 2012. The research sought to examine the extent of Popular Music Studies (PMS) undergraduate programmes in the United Kingdom, determine their key differences, report the findings and make recommendations to the funders about its future policies for PMS practitioners. We report our findings and the implications for PMS practitioners.
Number: 2
Keywords: Popular Music; Teaching; UK; Undergradute

The Continuum of Sexual Violence: Women’s Accounts of Victimization in Urban Nightlife - Kavanaugh, Philip R. (Feminist Criminology, 2013)
Despite the fact that a substantial amount of research has been conducted on sexual victimization among youth and young adults with active night lives, few of these studies have provided an analysis of the varied types of victimization that have occurred. I attempt to fill this gap with a qualitative analysis of women’s accounts of sexual victimization. Based on the substantive content of these women’s accounts, a three-part typology was generated, comprised of: (a) competing definitions of the situation, (b) opportunistic predation, and (c) involuntary incapacitation. Implications of the findings are discussed.
Publisher: SAGE Publications
Keywords: accounts; sexual assault; sexual victimization; unwanted sexual contact

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

Democratising the popular: the case of pop music in France and Britain - Looseley, David L. (International Journal of Cultural Policy, 2012)
The article represents the second phase of a comparative project on French and British cultural policy. The project's guiding hypothesis is that conceptualisations of the popular have been a crucial driver of policy change in France and Britain, raising complex issues about the nature of cultural democracy. The second phase, including this article, takes pop music as a case study for that hypothesis. The article explores three major issues. It asks how and why, in their attempts to rethink cultural democracy for the twenty-first century, French and British policy agencies have recognised pop music as a ‘democratic' form worthy of state support. It critically examines some of the theoretical issues this has raised, comparing and contrasting the ways in which the two national policy sets have variously represented pop as having symbolic, economic and social meanings. And it argues that what has been less adequately addressed is its aesthetic meaning.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2012.718917
Keywords: France and the UK; cultural democracy; pop music

Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Publisher: Routledge _eprint: https://doi.org/10.1080/19359705.2012.658013
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts

The Expansion of Punk Rock: Riot Grrrl Challenges to Gender Power Relations in British Indie Music Subcultures - DOWNES, JULIA (Women's Studies, 2012)
Publisher: Routledge _eprint: https://doi.org/10.1080/00497878.2012.636572

Black Women and Black Men in Hip Hop Music: Misogyny, Violence and the Negotiation of (White-Owned) Space - Rebollo-Gil, Guillermo; Moras, Amanda (Sociology Faculty Publications, 2012)

'Rock On': Women, ageing and popular music - Jennings, R.; Gardner, Abigail ('Rock On': Women, Ageing and Popular Music, 2012)
For female pop stars, whose star bodies and star performances are undisputedly the objects of a sexualized external gaze, the process of ageing in public poses particular challenges. Taking a broadly feminist perspective, 'Rock On': women, ageing and popular music shifts popular music studies in a new direction. Focussing on British, American and Latina women performers and ageing, the collection investigates the cultural work performed by artists such as Shirley Bassey, Petula Clark, Madonna, Celia Cruz, Grace Jones and Courtney Love. The study crosses generations of performers and audiences enabling an examination of changing socio-historical contexts and an exploration of the relationships at play between performance strategies, star persona and the popular music press. For instance, the strategies employed by Madonna and Grace Jones to engage with the processes and issues related to public ageing are not the same as those employed by Courtney Love or Celia Cruz. The essays in this insightful collection reflect on the ways that artists and fans destabilise both the linear trajectories and the compelling weight of expectations regarding ageing by employing different modalities of resistance through persona re-invention, nostalgia, postmodern intertextuality and even early death as the ultimate denial of age.

Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-2370.2011.00300.x
Keywords: Bibliographie; Nettoyer

Notions of popular culture in cultural policy: a comparative history of France and Britain - Looseley, David (International Journal of Cultural Policy, 2011)
The Devlin and Hoyle report, Committing to culture: arts funding in France and Britain, argues that the cultural policies of these two European neighbours have been steadily converging since the mid‐1990s but that their social and economic contexts are now quite different (e.g. youth unemployment, GDP, disposable income). The paper addresses this convergence‐within‐divergence by comparing how policy discourses have conceptualised popular culture in the two countries. It investigates the hypothesis that, in both, an engagement with popular culture has in fact been an important driver of change, albeit at different times and with different taxonomies. And it asks what light this comparison might shed on cultural policy thinking in the twenty‐first century.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2010.541907
Keywords: France; UK; cultural policy; history; popular culture

‘Guys! Stop Doing It!’: Young Women's Adoption and Rejection of Safety Advice when Socializing in Bars, Pubs and Clubs - Brooks, Oona (The British Journal of Criminology, 2011)
Concern about the increase in alcohol consumption amongst young women, drink spiking and drug-assisted sexual assault have culminated in a renewed focus on safety advice for young women. This paper examines young women's responses to safety advice, and their associated safety behaviours, by drawing upon interview and focus group data from a qualitative study with 35 young women (18–25 years) in relation to their safety in bars, pubs and clubs. The findings reveal that young women's behaviours were complex and contradictory in that they resisted, adopted and transgressed recommended safety behaviours. This raises interesting questions about both the practical and the theoretical implications of contemporary safety campaigns, challenging the prevailing focus on women's behaviour and the gendered discourse invoked by such campaigns.

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

A Safe Education for All: Recognizing and Stemming Harassment in Music Classes and Ensembles - Carter, Bruce Allen (Music Educators Journal, 2011)
This article addresses the pervasiveness of harassment in schools in the United States and presents ways to recognize and stem bullying in music classrooms. Music educators are in a unique position to recognize atypical behaviors in their students. Music educators who teach middle and high school ensembles often retain the same students in their classrooms over the course of many years. Because of the unique nature of the ensemble experience, coupled with the opportunity for extended instruction, music teachers can closely monitor the well-being of their students. However, music teachers should understand how difficult it may be for students who have been harassed to come forward with information about harassment. Sometimes harassment is overt and easy to recognize (e.g., name-calling, inappropriate gestures, graffiti). However, harassment can also occur in contexts that are not readily recognized but are just as hurtful. When students observe teachers taking a stand against bullying and harassment, they recognize the intention for a safe classroom. When students feel safe, they are more likely to ask questions and engage in class in dynamic and meaningful ways—both musically and nonmusically. Only when students feel safe can they learn. Music teachers need to gain a further understanding of various forms of harassment and further consider their role in creating a welcoming and secure environment.
Publisher: SAGE Publications Inc
Keywords: Bullying; Harassment; Music classrooms; Myriam

Music festival sponsorship: between commerce and carnival - Anderton, Chris (Arts Marketing: An International Journal, 2011)
Purpose – This paper aims to examine the cultural heritage of outdoor rock and pop music festivals in Britain since the mid‐1960s, and relates it to developments in, and critiques of, corporate sponsorship in the contemporary music festival sector. Design/methodology/approach – The paper uses extant research materials to construct an account of British music festival history since the mid‐1960s. It then draws upon Bakhtin's concept of the carnivalesque and the literature on sponsorship, experiential marketing and branding, in order to understand critiques of corporate sponsorship and the changing nature of the sector. Findings – Outdoor rock and pop music festivals were dominated by the ideologies of a “countercultural carnivalesque” from the late 1960s until the mid‐1990s. In the 1990s, changes in legislation began a process of professionalization, corporatization, and a reliance on brand sponsorships. Two broad trajectories are identified within the contemporary sector: one is strongly rooted in the heritage of the countercultural carnivalesque, while the other is more overtly commercial. Research limitations/implications – It is argued that experiential marketing and brand activation are key methods for achieving a balance between the competing aspects of commerce and carnival. Hence, festival organisers and sponsors need to understand the history of the sector and of their own events and attendees in order to use corporate sponsorship more effectively. Originality/value – This paper adds historical and theoretical depth to the debate between commerce and carnival within the music festival sector, and makes connections between cultural theory and the literature on sponsorship and branding.
Publisher: Emerald Group Publishing Limited
Keywords: Bakhtin; Branding; Carnivalesque; Counterculture; Music festivals; Sponsorship; United Kingdom

Popular Music and the State in the UK. Culture, Trade or Industry? by Martin Cloonan - Laing, Dave (Popular Music, 2011)

Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture - Strong, C. (2011)
Semantic Scholar extracted view of "Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture" by C. Strong

“Yes, I Do but Not with You”: Qualitative Analyses of Sexual/romantic Overture-Related Aggression in Bars and Clubs - Graham, Kathryn; Wells, Samantha; Bernards, Sharon; Dennison, Susan (Contemporary Drug Problems, 2010)
Assaultive and aggressive behaviors related to sexual overtures are common in commercial drinking establishments (bars, pubs, and clubs). In this article, we examined the thematic content of 251 incidents of verbal and physical aggression related to sexual/romantic overtures documented by researcher-observers in a study of Toronto bars and clubs. Aggression was examined as it emerged in the following stages of the social interaction process: (a) sexual/romantic overtures that began aggressively; (b) initiators of sexual/romantic overtures who became aggressive later in the social interaction process; (c) aggression by targets of overtures; and (d) aggression by third parties. From these thematic analyses we identify the distinctions between predatory and genuine overtures and explore the potential role of the effects of alcohol.
Publisher: SAGE Publications Inc

Comparative Gender and Institutions: Directions for Research - Chappell, Louise (Perspectives on Politics, 2010)
A comparative politics of gender offers an opportunity to consider in detail the operation of gender within political institutions. As such, it contributes to a deeper understanding of the roles and experiences of men and women within political institutions, of the policies, laws and norms that are the outcomes of these institutions, and of the relationship between these institutions and social actors. This essay proposes a multi-directional strategy for undertaking comparative gender and institutional research that includes taking account of similarities and differences within and across states, between states and international institutions, across space as well as across time. It argues that through this research strategy it is possible to gain a more nuanced understanding of gender processes and outcomes, which is valuable to those working both inside and outside political institutions to advance a women's equality agenda.
Publisher: Cambridge University Press

Managing Physical and Sexual Assault Risk in Urban Nightlife: Individual- and Environmental-Level Influences - Kavanaugh, Philip R.; Anderson, Tammy L. (Deviant Behavior, 2009)
In this article we use interview and direct observation data to examine the experiences of young people in two Philadelphia nightlife scenes, and the ways in which they manage risk of physical and sexual assault. Our analysis reveals several environmental-level factors that shape risk exposure, as well as a number of individual-level tactics used to manage risk. Our observations are discussed in terms of their implications for developing a risk management framework that accounts for the role of individual- and environmental-level factors in shaping victimization.
Publisher: Routledge _eprint: https://doi.org/10.1080/01639620902854639

The Promise and Pitfalls of Gender Mainstreaming - Sainsbury, Diane; Bergqvist, Christina (International Feminist Journal of Politics, 2009)
This article examines gender mainstreaming in Sweden, which is an interesting case because several favorable conditions make its implementation likely. It addresses two main questions: (1) to what extent has gender mainstreaming been implemented and (2) what are the consequences? The article first discusses the pros and cons of gender mainstreaming as reflected in the international feminist debate. It then briefly describes the favorable conditions of the Swedish case and subsequently maps out the introduction of gender mainstreaming since 1994, focusing on the process and its politics. It concludes with a discussion of the Swedish experience in terms of the promise and pitfalls of gender mainstreaming identified in the feminist debate and the implications of the Swedish case for feminist theorizing on gender mainstreaming.
Publisher: Routledge _eprint: https://doi.org/10.1080/14616740902789575
Keywords: Sweden; feminist theory; gender equality policies; gender mainstreaming; gender politics

Loyalty and Longevity in Audience Listening: Investigating Experiences of Attendance at a Chamber Music Festival - Pitts, Stephanie E.; Spencer, Christopher P. (Music and Letters, 2008)
There is currently much concern among arts organizations and their marketing departments that audiences for classical music are in decline, yet there has been little investigation so far of the experiences of long-term listeners that might yield insights into audience development and retention. This paper presents a case study of the Music in the Round chamber music festival, conducted over a three-year period that included the retirement of the host string quartet, the appointment of a new resident ensemble, and associated changes in audience attitudes and priorities. Questionnaire and interview data revealed the challenges faced by audience members in shifting their loyalty to a new ensemble and reappraising their own listening habits and stamina. The interaction between individual listening and collective membership of an audience is discussed, and the potential considered for understanding classical concert-goers as ‘fans’ or ‘consumers’.

[POSITIF: à ajouter ?|The Social Construction of Female Sexuality in a Sexualized Work Environment (SWE): The Case of a Comedy Club - Philaretou, Andreas G.; Young, Christi L. (Sexual Addiction & Compulsivity, 2007)
This qualitative investigation seeks to identify the sociocultural determinants and psychoemotional ramifications of essentialist gender scripting on female employees in a sexualized work environment (SWE), such as a comedy club. Sexualized work environments incorporate work and sexuality and exist on a continuum according to the frequency and intensity of the sexual economic exchange that takes place within them. In this study, interviews were conducted with 13 female employees at a comedy club in Southwest Michigan to explore the social construction of female sexuality in such an environment.
Publisher: Routledge _eprint: https://doi.org/10.1080/10720160601150139
Keywords: Sophie-Anne

The Girl Hunt: Urban Nightlife and the Performance of Masculinity as Collective Activity - Grazian, David (Symbolic Interaction, 2007)
The purpose of this article is to document the collective nature of gender performance and sexual pursuit, activities typically associated with individual rather than group behavior. Drawing on narrative accounts, I analyze how young heterosexual male students employ the power of collective rituals of homosociality to perform sexual competence and masculine identity by “girl hunting” in the context of urban nightlife. These rituals are designed to reinforce dominant sexual myths and expectations of masculine behavior, boost confidence in one's performance of masculinity and heterosexual power, and assist in the performance of masculinity in the presence of women. This analysis illustrates how contemporary courtship rituals operate as collective strategies of impression management that men perform not only for women but for other men. In doing so, interaction rituals associated with the girl hunt reproduce structures of inequality within as well as across the socially constructed gender divide between women and men.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1525/si.2007.30.2.221

‘Loaded’: indie guitar rock, canonism, white masculinities - Bannister, Matthew (Popular Music, 2006)
Indie alternative rock in the 1980s is often presented as authentically autonomous, produced in local scenes, uncaptured by ideology, free of commercial pressures, but also of high culture elitism. In claiming that the music is avant-garde, postmodern and subversive, such accounts simplify indie's historical, social and cultural context. Indie did not simply arise organically out of developing postpunk music networks, but was shaped by media, and was not just collective, but also stratified, hierarchical and traditional. Canon (articulated through practices of archivalism and connoisseurship) is a key means of stratification within indie scenes, produced by and serving particular social and cultural needs for dominant social groups (journalists, scenemakers, tastemakers, etc.). These groups and individuals were mainly masculine, and thus gender in indie scenes is an important means for deconstructing the discourse of indie independence. I suggest re-envisioning indie as a history of record collectors, emphasising the importance of rock ‘tradition’, of male rock ‘intellectuals’, second-hand record shops, and of an alternative canon as a form of pedagogy. I also consider such activities as models of rational organisation and points of symbolic identification.
Publisher: Cambridge University Press

Lesbian Lacunae: Invisible Spaces in Dance Education - Mozingo, Karen A. (Journal of Dance Education, 2005)
Recent research about sexuality and dance has begun to address the needs of gay male dancers, yet the needs of lesbian dancers have remained mostly absent from scholarly discourse. Exploring the lesbian lacunae, or invisible spaces of dance education, reveals the personal, political, and pedagogical implications of their existence within the dance community. The experiences of lesbian dancers “on the fringe” combined with new approaches to acknowledging lesbian artists and perspectives within dance history suggest the need for re-envisioning lesbian invisibility as a “liminal presence” within dance. In addition, ways dance educators can reduce the effects of heterocentrism within their institutions and celebrate the contributions of lesbian artists and educators to the field are proposed. By reconfiguring the invisibility of lesbian dancers as a liminal presence, we make visible the borders and limits of the dance profession's notions of sexuality and gender, acceptance and equality, and thereby strengthen our potential for dancing beyond them.
Publisher: Routledge _eprint: https://doi.org/10.1080/15290824.2005.10387286
Keywords: Bibliographie; Nettoyer

Rehearsing Heterosexuality: "Unspoken" Truths in Dance Education - Risner, Doug (Dance Research Journal, 2002)
Keywords: Bibliographie; Nettoyer

All rock and roll is homosocial: the representation of women in the British rock music press - Davies, Helen (Popular Music, 2001)
The British rock music press prides itself on its liberalism and radicalism, yet the discourses employed in music journalism exclude women from serious discussion both as musicians and as fans. In particular, the notion of credibility, which is of vital importance to the ‘serious’ rock music press, is constructed in such a way that it is almost completely unattainable for women.The most important and influential part of the British music press was until recently its two weekly music papers, Melody Maker (MM) and the New Musical Express (NME), both published by IPC magazines. The NME, launched in 1949, contains reviews, concert information and interviews with performers and describes itself as ‘a unique blend of irreverent journalism and musical expertise’ (www.ipc.co.uk). MM, which started life in 1926 as a paper for jazz musicians, had similar content but a greater emphasis on rock, as opposed to pop, music. It was relaunched in 1999 as a glossy magazine, before ceasing publication or, as IPC put it, merging with the NME, in December 2000.
Publisher: Cambridge University Press

Vanishing in Your Face: Embodiment and Representation in Lesbian Dance Performance - Kuppers, Petra (Journal of Lesbian Studies, 1998)
Lesbian dance performance has to come to terms with the cultural invisibility of the lesbian body, and the dichotomy of traditional gender representation. This paper charts strategies for the play with the invisible, the grotesque and the liminal in the dance performance of three UK-based choreographers: Emilyn Claid, Yael Flexer and Kate Lawrence. Their performances create tension between the role and the body, between the public and the private, and it is this tension that points towards alternative representational strategies.
Publisher: Routledge _eprint: https://doi.org/10.1300/J155v02n02_04

Racial Harassment, Sexual Harassment, and the Expressive Function of Law Case - Mullender, Richard (Modern Law Review, 1998)
Keywords: Sophie-Anne

A TOP NIGHT: Social Protest, Masculinity and the Culture of Drinking Violence - TOMSEN, STEPHEN (The British Journal of Criminology, 1997)
Although a wide research literature suggests a regular connection between drinking, violence and social disorder, much doubt remains as to the actual nature and significance of this link. Some strong insights into this are provided by a dual consideration of the tie between masculine social identity and heavy group drinking, and the importance of issues of male honour in the social interaction that leads to much violent behaviour. But as well as this, information from the author's detailed ethnographic study of assaults in public drinking venues illuminates the subjective experience of participation in acts of disorder and violence. This is filtered through understandings of certain forms and aspects of popular leisure as entailing social protest and resistance to middle class morality. Although masculinist and frequently destructive, this violence is interpreted by many drinkers as providing a liberating and attractive sense of release, group pleasure and carnival.

Sexual Harassment of Women Journalists - Walsh-Childers, Kim; Chance, Jean; Herzog, Kristin (Journalism & Mass Communication Quarterly, 1996)
A survey of 227 women newspaper journalists revealed that more than 60 percent believe sexual harassment is at least somewhat a problem for women journalists; more than one-third said harassment has been at least somewhat a problem for them personally. Two-thirds experience nonphysical sexual harassment at least sometimes, and about 17 percent experience physical sexual harassment at least sometimes. News sources were the most frequent harassers, and harassment ranged from degrading comments to sexual assault._
Publisher: SAGE Publications Inc
Keywords: Journalisme; Myriam; journalism

Freedom and Outrage in Art Education - Lankford, E. Louis (Journal of Aesthetic Education, 1994)
Publisher: University of Illinois Press
Keywords: Myriam

The changing role of women executives in the recording industry - Parsons, Patrick R. (Popular Music and Society, 1988)
Publisher: Routledge _eprint: https://doi.org/10.1080/03007768808591332

Women and Rock Music - Harding, Deborah; Nett, Emily (Atlantis: Critical Studies in Gender, Culture & Social Justice, 1984)
Rock music is the most misogynistic and aggressive form of music currently listened to. Women's place in it since the 1950's is described and analyzed in this article. Rock music was originally a working-class male challenge to the established symbolic order. In terms of the revenue generated by the industry thirty years later, it is the most important cultural expression of popular music. The enterprise is almost exclusively male, the majority of listeners are male, and even though women singers contributed in the early 1960's, there have been only a few female performers. An analysis of feminine representations in rock music lyrics and album covers in 1981 reveals a variety of male-identified images of women. In view of the cultural context in which rock music originated and the industry developed, the recent penetration by a few more women into the industry raises questions about whether numbers will continue to increase and, even if they do, whether rock music constitutes an appropriate voice in which women can authentically express themselves.
Number: 1
Keywords: Music; Myriam; Rock Music

Témoigner de son agression à caractère sexuel sur Internet

THE STATUS OF WOMEN IN THE CANADIAN ARTS AND CULTURAL INDUSTRIES - RESEARCH REVIEW 2010-2018

The Changing Roles of Female Visual Artists in Morocco - Azhar, Samir El
Female artists are actively participating in the development and growth of visual arts in Morocco. This article seeks to highlight their important contribution in the Moroccan visual arts. It deals with the access of women to the field of visual art, delineates successive categories for understanding the types of work female artists have engaged in since the independence of the country in 1956, and the challenges that these artists have been facing. It focuses on the artistic experiences of specific artists, believed to be, representative of some historical era or artistic trend. Moreover, it tries to put these artists into a cultural and historical framework to contextualize their artistic production.

Planning and Management for Public Health Impacts at Outdoor Music Festivals: An International Study - Earl, Cameron; Parker, Elizabeth; Capra, Mike (Environmental Health)
In 2000 the Glastonbury Festival in England experienced an unprecedented invasion of gatecrashers that severely compromised public health and safety. This incident identified the need for a comprehensive review of planning and management procedures for that event. In order to undertake this review, the 2001 event was cancelled. Upon its return in 2002, the event demonstrated considerable improvements in health and safety with the main features being tighter security and a more secure perimeter fence. Advancements such as these have continued at each subsequent event, with the 2004 festival considered the safest to date. The Glastonbury Festival provides a model for successful management of health and safety issues for large public events. This success was made possible by the collaborative efforts of the event organiser and government agencies, in particular the Mendip District Council. This event demonstrates how the licensing process can be a useful tool to encourage good practice in public health and safety issues for large outdoor music festivals.
Publisher: Environmental Health Australia (EHA)
Keywords: Glastonbury Festival; Music festival programs; Music festivals–Management; Outdoor music festivals (OMF); Public health; Risk assessment; Social movements; Special events–Management

The #E-Too Movement: Fighting Back Against Sexual Harassment in Electronic Sports - Holden, John T; Iii, Thomas A Baker; Edelman, Marc (ARIZONA STATE LAW JOURNAL)
Competitive video gaming or esports has captured the attention of hundredsof millions ofpeople acrossthe globe. With that attentionhas come billions of dollars' worth of investment and promotion. But, it has also exposed an underlying toxic environment that features widespreadsexual andgender harassment. This pervasive culture of harassment threatens to derailthe esports industry and mars the promise of gender equity in one of the few competitive "sports"where physical strength, agility and body size do not dictate success. In this Article, we examine the rise of competitive gaming, and provide an in-depth analysis of the pervasive issue of harassment that permeates esports. We then propose a series of tangible reforms that would hold harassers and their corporate accomplices accountablefor their harassingbehavior.
Keywords: Irina

Optique culture – Numéro 93. Février 2024 – Les professions de la culture et des communications au Québec en 2021 - Marc-Andy Lubin

Gendered Precarity and Labor Organizing in the South Indian Film Industries - Mini, Darshana Sreedhar
Keywords: Irina

Une révolution culturelle en France ? - Ritland, Sara Prytz
Keywords: Irina

Critical Analysis of Sexual Harassment at Work Place (Prevention, Prohibition and Redressal) Act, 2013 with Special Emphasis to Film Industry - S', Anjana; George, Meera Elsa
Gone are the days where only men were the breadwinners of a family. With opportunities expanding and people moving forward into a contemporary world, gender disparity regardingemployment has become a thin line. We are in an era where both men and women workfor a living and contribute to theirfamily. Women are now coming forward and stepping into powerful positions and leaving their marks in various industries. However, there are many issues that demotivate women from coming forward. One such major issue is the absence of a healthy and safe working environment. Sexual Harassmentat Workplace is a violation of a woman's fundamental rights under Article 15, 19 and 21. It makes a woman insecure and causes severe mental trauma which in turn makes her quit the job or affects her self-confidence. Women are not sex toys for pleasure or the weak vulnerable section of humankind, but years of the patriarchalsystem that silenced women have resultedin women being subject to such exploitation.
Keywords: Irina

Cadre de l'édition. Des inégalités femmes-hommes toujours fortes - Serry, Hervé
Keywords: Irina

Valuing live music: The UK Live Music Census 2017 report - Webster, Emma; Brennan, Matt; Behr, Adam